Degree-Based Topological Indices of Generalized Subdivision Double-Corona Product - Ying Wang; Muhammad Waheed; Muhammad Kamran Jamil; Syed Mazhar Shah; Adnan Aslam; Hamideh Aram (Journal of Chemistry)
Graph operations play an important role in constructing complex network structures from simple graphs. Computation of topological indices of these complex structures via graph products is an important task. In this paper, we generalized the concept of subdivision double-corona product of graphs and investigated the exact expressions of the first and second Zagreb indices, first reformulated Zagreb index, and forgotten topological index (F-index) of this graph operation.